Efforts to Increase Students' Learning Motivation in Al-Qur'an Hadith Lessons About the History of the Decline and Writing of the Qur'an with CBSA - Imam Tabroni; Elda Sri Lestari; Heni Hermaningsih SM (Jurnal Multidisiplin Madani, 2022)
This study aims to increase motivation to learn Al-Qur'an Hadith in class X MA YPMI Wanayasa on Derivative History and Al-Qur'an Writing. This research method uses classroom action research (action research). Actions are carried out in 2 cycles. Each cycle consists of several stages, namely: planning, action, observation and reflection. The subjects in this action were all students of class X MA YPMI Wanayasa as many as 25 students consisting of 13 female students and 12 male students. The reason is because class X students experience problems in learning outcomes of Al-Qur'an Hadith subjects, namely the number of students who do not meet the Minimum Completeness Criteria (KKM) determined by the madrasa. Collecting data using documentary techniques in the form of the results of the subjects of the Qur'an Hadith, History of Setbacks and Writing of the Qur'an as well as the results of learning the material before the action or pre-cycle. Student learning outcomes are known by test techniques, interview techniques to determine the state of the problem before the action, and observation techniques to determine student activities in learning. The results showed that learning using the CBSA approach in the History of Derivation and Writing of the Qur'an and in the subjects of Al-Qur'an Hadith could increase students' learning motivation. Students are given the opportunity to be actively involved physically, mentally, intellectually, and emotionally. Based on the results of this study, it is hoped that it can become information and input for teaching staff, especially those who teach Al-Qur'an Hadith subjects to further improve the quality of learning by using active, innovative, creative and fun learning